VD_FINDINFO Jug / 2015 / 351 vom 18. Juni 2015 - VD Tribunal cantonal (2015)
RESPONSABILITÉ DES ORGANES D'UNE SOCIÉTÉ, DILIGENCE, FIDÉLITÉ, LIEN DE CAUSALITÉ, DOMMAGE, CONSORITÉ | 717 CO, 754 CO, 260 LP